Cross-cultural adaptation of COSTaRS Practice Guidelines for the management of chemotherapy-associated nausea and vomiting in cancer patients (癌症患者化疗相关性恶心、呕吐症状管理实践方案的跨文化调适研究) - LI Jiaji (李佳霁); ZHANG Jing (张敬); XU Jingjin (徐京巾); LI Ye (李野); TANG Ling (唐玲) (中西医结合护理)
Objective To translate, synthesize and review the Canadian Oncology Symptom Triage and Remote Support (COSTaRS) Practice Guidelines on Nausea and vomiting by expert committee to achieve semantic, idiomatic, experiential and conceptual equivalence between Chinese and English versions. Methods Forward translation, comprehensive coordination, reverse translation and expert committee review of the English version of COSTaRS were carried out to form the pre-test version of Chinese COSTaRS. A self-designed survey table on the applicability of recommendations of the COSTaRS Practice Guidelines for nausea and vomiting was conducted. Nurses are required to evaluate the feasibility and acceptability of the application of each item of this guideline to patients in their own institution according to their own expertise. Results A total of 80 questionnaires were sent out, among which 78 were valid, and the recovery efficiency of the questionnaires was 97. 50%. The nursing staff had a high participation rate. The acceptability and feasibility of the guidelines were scored, and the results showed that the nursing staff had a high evaluation of the guidelines. Conclusion The cross-cultural adapted Chinese version of COSTaRS is suitable for the practice management of nausea and vomiting in cancer patients in the Chinese cultural context, and can provide evidence-based best practice information for the improvement and prevention of nausea and vomiting symptoms in cancer patients. (目的 对加拿大肿瘤症状远程管理项目(COSTaRS)恶心呕吐实践指南进行翻译、合成和专家委员会评审, 实现中英文版本之间的语义、习语、经验及概念对等。方法 对COSTaRS英文版进行正向翻译、综合协调、反向翻译、专家委员会评议, 形成中文COSTaRS预试验版, 将自行设计《COSTaRS恶心和呕吐实践指南推荐意见适用性调研表》展开调研, 要求护士根据自身专业判断对本指南各条目在其所在机构的患者进行应用是否具有可行性和可接受性进行评价。结果 共发放80份问卷, 其中有效问卷78份, 问卷回收有效率为97. 50%, 护理人员参与度较高。对指南内容的可接受性和可行性进行评分, 结果显示护理人员对其评价较高。结论 跨文化调适后的COSTaRS中文版适用于中国文化背景下癌症患者恶心呕吐实践管理方案, 可提供改善和防治癌症患者恶心呕吐症状提供基于循证的最佳实践信息。)